The role of awareness in Islamic bank patronizing behavior of mauritanian: an application of TRA - Mahmoud, Limam O.M.; Abduh, Muhamad (IIUM Institute of Islamic Banking and Finance, 2014)
This paper is aimed at examining the role of awareness and the applicability of the theory of reasoned action (TRA) in predicting the intention of people to patronize Islamic Banks in Mauritania. A total of 227 respondents were involved and structural equation model was used to measure the relationship between the exogenous and endogenous variables in the model. The results have shown that TRA is a valid model in predicting the intention of Mauritanian to patronize Islamic banks in Mauritania. Attitude and subjective norm were found to have a positive influence upon the intention to patronize Islamic banks. It was also proven that awareness has a positive and significant influence upon the attitude and thus influences the intention of Mauritanian to patronize Islamic bank.